2013
DOI: 10.1016/j.tet.2012.12.058
|View full text |Cite
|
Sign up to set email alerts
|

Multisubstituted benzo[b]furans through a copper- and/or palladium-catalyzed assembly and functionalization process

Abstract: Full details as well as the study of the scope, limitations, and further elaboration of a straightforward approach to the synthesis of 2,5,7-trisubstituted benzo[b]furans from 2-bromo- and 2-chloro-6-iodo-4-substituted phenols through a consecutive copper- and/or palladium-catalyzed assembly and functionalization process is described. Functionalization at the C(7) position is carried out by Suzuki-Miyaura cross-coupling, alkynylation, alkenylation, and C-N bond forming reactions. A one-pot protocol for the syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 103 publications
0
14
0
Order By: Relevance
“…The E -geometry around the vinylic framework of these chalcones was confirmed by the two sets of doublets around δ = 7.48 and 7.89 ppm, with coupling constant values J trans = 15.5 Hz, which correspond to the H-α and H-β, respectively. The 2-alkyl/aryl-substituted benzofurans were previously synthesized via the palladium catalyzed cross coupling-heteroannulation of the 2-bromo/iodophenol derivatives with terminal acetylenes [ 21 , 22 , 23 ]. It has, however, been observed before that the 2-bromo/iodophenol, substituted with an α,β-unsaturated carbonyl moiety fails to undergo Sonogashira cross-coupling with terminal alkynes when tetrakis(triphenylphosphine)palladium(0) (PdPPh 3 ) 4 was used as the active Pd(0) source [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…The E -geometry around the vinylic framework of these chalcones was confirmed by the two sets of doublets around δ = 7.48 and 7.89 ppm, with coupling constant values J trans = 15.5 Hz, which correspond to the H-α and H-β, respectively. The 2-alkyl/aryl-substituted benzofurans were previously synthesized via the palladium catalyzed cross coupling-heteroannulation of the 2-bromo/iodophenol derivatives with terminal acetylenes [ 21 , 22 , 23 ]. It has, however, been observed before that the 2-bromo/iodophenol, substituted with an α,β-unsaturated carbonyl moiety fails to undergo Sonogashira cross-coupling with terminal alkynes when tetrakis(triphenylphosphine)palladium(0) (PdPPh 3 ) 4 was used as the active Pd(0) source [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Once having elucidated the homogeneous nature of the employed catalyst, the second question was to clarify if the presented heteroannulation leading to benzofurans was based on an initial copper‐catalyzed Sonogashira reaction (or catalytic Stephens–Castro reaction), as previously reported,8a–c,fg,k or if other processes were really taking place.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, most Cu‐catalyzed coupling reactions are performed by using 5–20 mol% of the copper source 7. This is particularly true for copper‐catalyzed tandem reactions, such as the heteroannulation‐type reaction of 2‐iodophenols with arylacetylenes leading to benzofurans,8 a field where an initial palladium‐free Sonogashira‐type coupling is assumed to occur 8a–c,fg,k…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, the Arcadi group also reported that a tandem reaction via Sonogashira coupling of 2‐bromo‐6‐iodephenol and annulation afforded 7‐bromobenzofuran derivatives. Moreover, they also reported that a Pd‐catalyzed coupling reaction of this product with arylboronic acids afforded 7‐arylbenzofuran derivatives (Scheme b) . These synthetic strategies required a halogen atom at the corresponding position of the starting material.…”
Section: Introductionmentioning
confidence: 99%